Working across lines : resisting extreme energy extraction - Grosse, Corrie, 1990- (University of California Press, 2022)
"How are communities uniting against fracking and tar sands to change our energy future? Working across Lines offers a detailed comparative analysis of climate justice coalitions in California and Idaho-two states with distinct fossil fuel histories, environmental contexts, and political cultures. Drawing on extensive ethnographic evidence from 106 in-depth interviews and three years of participant observation, Corrie Grosse investigates the ways people build effective energy justice coalitions across differences in political views, race and ethnicity, age, and strategic preferences. This book argues for four practices that are critical for movement building: focusing on core values of justice, accountability, and integrity; identifying the roots of injustice; cultivating relationships among activists; and welcoming difference. In focusing on coalitions related to energy and climate justice, Grosse provides important models for bridging divides to reach common goals. These lessons are more relevant than ever"--